Characteristics and Mechanism of Gelatination of Dangke Curd by Physico-chemical Properties and Microstructure - R. Malaka; S. Baco; K. I. Prahesti (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
Dangke is a dairy product which is known as traditional cheese of Enrekang District, South Sulawesi. It is made by heated clotting of buffalo, cow, goat or sheep milk with addition of papaya sap (Carica papaya) or pineapple juice. Dangke has been well known by South Sulawesi community but information is very limited regarding to its characteristics with standardized quality. The objective of this study was to produce dangke with standardized quality (physical properties, chemical properties and microstructure) so that, at the end, this product can become a certified product having specific characteristics, which is in turn can be introduced nationally or internationally as a genuine product of South Sulawesi. It is expected that this Indonesian cheese will be increasingly popular as Cheddar (England); Gouda and Edan (Netherland); Emmental and Gruyere (Swiss); Limburger, Cammembert and Brie (France); Gorgonzola, Mozzarella, and Romano (Italy); Brunost (Norway); Damiati (Egypt) and so on. Dangke was prepared using 18 L of raw whole milk and heated at 75, 80, 85, 90, 95 and 100oC for 1 minute and coagulated by addition of papaya sap 0.3%, 0.4% and 0.5%, and added 1% of salt. Curd was poured to Dangke cheese template and pressed until compact. The cheese was packaged riped at approximately 5oC. Dangke was evaluated towards physical properties (hardness, pH, elasticity), chemical properties (percentages of fat, protein, and lactic acid) and microstructure. Hardness and elasticity determined by rheometer, pH values measured by using a Hanna-pH-meter. Microstructure was viewed by a fasecontrast and light microscope in 1000 x of magnification. Level of fat and protein were analyzed by proximate analysis. Percentage of lactic acid was evaluated by titratable acidity. Result of this study showed that higher heating temperature decreased protein and fat contents, as well as lactose but increased pH and lactic acid. The best structure and the highest protein content of dangke was obtained by heating temperature of 75oC with 0.5% papaya sap.